Illuminating inclusive pedagogy in Thai EFL classrooms: critical perspectives and practices in higher education - Buarattana Attachoo,; Pariwat Imsa-Ard, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social diversity can be a prevalent feature in any classroom, where a mix of learners from varied backgrounds is now the norm. Such dynamics intricately shape a student’s prospects for success or failure. In Thailand, as in educational settings worldwide, educators are contending with growing diversity among their students, encompassing the instruction of learners with special needs and diverse backgrounds. This qualitative study explored how eight EFL university instructors actively constructed their identities as inclusive practitioners while contending with the implementation of inclusive education policies. The data were sourced from individual semi-structured interviews. Through the lens of sociocultural and critical framing within identity theory, their identity construction was meticulously examined as both EFL educators and advocates for inclusive education. This study emphasises the pivotal roles of discourse, self-positioning, and social context as fundamental processes in forming teacher identity. The findings revealed that some EFL instructors suggested a uniform treatment of learners within the classroom, acting in different roles to navigate the complexities of inclusivity in EFL classrooms, and an emphasis on the importance of empathy, openness, and flexibility in fostering inclusive learning environments. This study highlights the crucial implications of fostering inclusive education in EFL classrooms by advocating for proactive communication, differentiated instruction, and ongoing support. These measures are essential for creating equitable learning environments, especially for students with special educational needs.